Effect Of Alley Size And Hedgerow Pruning Interval On Phenology And Yield Of Okra [Abelmoschus Esculentus (L.) Moench] In Hill Slope (Bangladesh Journal of Agricultural Research, 2011)
An experiment was conducted at the Hill Agricultural Research Station, Khagrachari from May 2002 to November 2004 to find out the effect of alley size (3.0 , 4.0, and 5.0 m) and hedgerow pruning interval (1, 2, and 3 months) on phenology and fruit yield of okra in hill slope condition during the rainy season. The highest fruit yield (16.14 t/ha) was produced by the plants grown in 3.0 m size alley. In case of hedgerow pruning interval, the highest yield (16.07 t/ha was recorded from 2 months pruning interval and it was significantly different with other two pruning intervals. The treatment combination of 3.0 m size alley with I month pruning interval produced significantly highest yield (17.67 t/ha). The highest gross return (Tk.176700/ha), net return (Tk.120380/ha) and BCR (3.14) were also found from the same treatment though highest cost of production was involved in this treatment.   Key words: Alley size; pruning interval; phenology; okra yield; cost benefit. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9238 BJAR 2011; 36(1): 143-150